CRIMINOLOGICAL AND CRIMINAL LAW ANALYSIS OF JUVENILE VIOLENT CRIME - Karpovs, Vladimirs (Administrative and Criminal Justice, 2018)
In this article the author studies new forms of destructive violent forms of crimes and other deviations among minors. Among the new forms of destructive aggression in the modern world, the author selected the following: violence in schools (physical and mental), cyberbullying, inducement of minors to suicide. The main purpose of this research is to study the materials of criminal cases, police reports in the world about such violations in order to form the reasons for their commission, as well as offer specific measures of social control and their prevention. The scientific novelty of the study lies in the criminological study of such social phenomena. As one of the main conclusions, we are talking about the need to create an updated and detailed policy for the social control of such deviations.